Business model and innovation strategy of a Brazilian food company - Donadon, Frederico Andreis Beneli; Santos, David Ferreira Lopes [UNESP] (Universidad Icesi, 2020)
This study aimed to analyze the business model, the strategy, and the innovation capacity of a Brazilian food industry. To this end, methodologically, a case study was conducted based on data collected by interviews marked by the Business Model Canvas and Innovation Octagon, which were validated with the software IRAMUTEQ. The results constitute a business model supported by an internal structure of research and development, aimed at the launch of new products with greater added value, directed towards the demands of consumption, and regulation. This competitive scenario differs from the results of other research, mainly with regard to the low level of investment in research and development, the incremental nature of innovations, the dependence on basic commodities, and the lack of effectiveness in innovative activities.
Modelo de negócio e estratégia de inovação de uma empresa brasileira de alimentos
Keywords: Brazil; Food company; Innovation strategies; Innovative capacity